Scaffolding Instruction of Nahwu and Sharaf through the Kitab al-Kamal - Saribudin Saribudin; Isnol Khotimah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the limited research on the implementation of the Kitab Al-Kamal method in Arabic grammar learning, despite its significant role in strengthening students’ understanding of nahwu and sharaf in Islamic educational contexts. This study aims to explore the implementation process of the Kitab Al-Kamal method and analyze its impact on students’ grammatical comprehension and learning engagement. A qualitative case study design was employed, involving one Arabic language teacher and a group of students selected through purposive sampling. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using thematic analysis based on an interactive model of data analysis. The findings reveal that the Kitab Al-Kamal method contributes significantly to enhancing students’ grammatical awareness, analytical skills in sentence structure, and active participation in learning. The results also indicate a shift in students’ learning behavior from passive memorization to active and independent understanding. These findings support the theoretical perspective that structured and scaffolded learning approaches can improve language comprehension. The study concludes that the Kitab Al-Kamal method plays a crucial role in strengthening students’ mastery of nahwu and sharaf. The implications include theoretical contributions to Arabic language pedagogy and practical recommendations for educators to adopt structured, gradual, and interactive learning models. This study also suggests opportunities for future research on the integration of traditional Arabic grammar learning methods with digital learning media.